Pregnant woman awareness of obstetric danger signs in developing country: systematic review - Esti Yunitasari; Filomena Matos; Hakim Zulkarnain; Dewi Indah Kumalasari; Tiyas Kusumaningrum; Tantya Edipeni Putri; Ah. Yusuf; Nining Puji Astuti (BMC, 2023)
Abstract Background Mother's awareness of obstetric danger signs is the degree of a pregnant woman to fully utilize her knowledge of the signs and symptoms of complications of pregnancy, which helps the mother and family to seek medical help immediately. High maternal and infant mortality rates in developing countries are due to a combination of a lack of quality, resources and access to health services coupled with mother's lack of awareness. The purpose of this study was to collect current empirical studies to describe the pregnant women awareness about the obstetric danger sign in developing country. Method This review employed the Prisma-ScR checklist. The articles searched in four electronic databases (Scopus, CINAHL, Science Direct, Google Scholar). Variables that used to search the articles (pregnant woman, knowledge, awareness, danger signs pregnancy). The Framework used to review is PICOS. Result The results of the article found 20 studies which met inclusion criteria. The determinants were high educational status, more pregnancy experience, more ANC visit, and labour in the health facility. Conclusion The level of awareness is low to medium, only some have fair awareness, in which related to determinant. The recommended effective strategy is to improve the ANC program by assess the risk of obstetric danger sign promptly, assess the barrier of health seeking related to the family support, i.e. the husband and the elderly. Additionally, use MCH handbook or mobile application to record the ANC visit and communicate with the family.